Preparation for IELTS - Gough, Chris (Tổng hợp Tp. Hồ Chí Minh; Công ty Nhân Trí Việt, 2010)
Một bộ gồm Course Book, Workbook, 3 Mock Tests và 1 đĩa MP3. (giá trọn bộ 396.000); This module is in two sections. The first section engages students in a topic and pre-teaches key vocabulary, before focusing on a key skill or particular IELTS exam technique. The second section practises the skill.